Incidence du Contexte Culturel sur les Intérêts d'Etudiants Francophones Québécois et acadiens - Desruisseaux, Jean-Claude; Tétreau, Bernard; Trahan, Michel (Canadian Journal of Counselling and Psychotherapy, 2011)
The students were presented with the 102 colour slides of the Visual Interest Test (VIT), a non-verbal inventory showing workers of both sexes performing real-life occupational tasks. The Cronbach alpha coefficients ranged from .83 to .93 among the six scales (RIASEC) for both groups. No significant differences were found on any scale between the two cultural groups or between the same sex groups across cultures. However, significant differences between boys and girls, on all but the Investigative scale, corroborated the hypothesis that, in interest measurement, gender differentiation transcends cultural distinctions.